Economic importance of the Belgian ports: Flemish maritime ports, Liège port complex and the port of Brussels - Report 2014 - George van Gastel (National Bank of Belgium, 2016)
This paper is an annual publication issued by the Microeconomic Analysis service of the National Bank of Belgium. The Flemish maritime ports (Antwerp, Ghent, Ostend, Zeebrugge), the Autonomous Port of Liège and the port of Brussels play a major role in their respective regional economies and in the Belgian economy, not only in terms of industrial activity but also as intermodal centers facilitating the commodity flow. This update paper1 provides an extensive overview of the economic importance and development of the Flemish maritime ports, the Liège port complex and the port of Brussels for the period 2009 - 2014, with an emphasis on 2014. Focusing on the three major variables of value added, employment and investment, the report also provides some information based on the social balance sheet and an overview of the financial situation in these ports as a whole. These observations are linked to a more general context, along with a few cargo statistics. Annual accounts data from the Central Balance Sheet Office were used for the calculation of direct effects, the study of financial ratios and the analysis of the social balance sheet. The indirect effects of the activities concerned were estimated in terms of value added and employment, on the basis of data from the National Accounts Institute. As a result of the underlying calculation method the changes of indirect employment and indirect value added can differ from one another. The developments concerning economic activity in the six ports in 2013 - 2014 are summarised in the table on the next page: In 2014 the growth of maritime traffic in the Flemish sea ports was once again due solely to developments in the port of Antwerp. However, that did not necessarily mean that direct value added followed the same trend: except for the port of Zeebrugge, all other lemish ports recorded an increase. Direct employment is continuing to decline, except in the port of Ghent where it remains steady. Investment appears to be picking up, after last year's weak figures. Cargo traffic in the ports of Liège and Brussels was up in 2014, but that did not result in any increase in value added. The decline in direct employment also persisted, certainly in the port of Liège. This report provides a comprehensive account of these issues, giving details for each economic sector, although the comments are confined to the main changes that occurred in 2014. This report is available for download at the following address http://www.nbb.be.
Keywords: 330